Upaya peningkatan kualitas yoghurt set dengan penambahan pati kimpul (Xanthosoma sagittifolium) - Sari, Dewiarum; Purwadi, Purwadi; Thohari, Imam (Faculty of Animal Science, Universitas Brawijaya, 2019)
The purpose of this research is to find out difference between the addition of kimpul starch (Xanthosoma sagittifolium) and incubation time towards the total acid, viscosity, syneresis, water content and water holding capacity of yoghurt set. Yoghurt set was made from cow's milk with the addition of 2% of bacterial starters and addition of kimpul starch (0, 1, 2, and 3%) also all treatments in the incubation with room temperature (± 23oC) for (24 hours, 32 hours, 40 hours and 48 hours). The variables observed were the total acid, viscosity, syneresis, water content and water holding capacity. The method used in this research is 4x4 factorial experiment with Completely Randomized Design (RAL) with 3 times replications, and continued with Duncan's New Multiple Range Test (DMRT). The results showed that the addition of kimpul starch highly significant different (P≤0.01) on syneresis and water content decline, as well as total acid, viscosity and water holding capacity escalation. The incubation time highly significant different (P≤0.01) on syneresis and water content decline, as well as total acid, viscosity and water holding capacity escalation. The interaction between addition of starch and incubation time is not significantly different (P>0.05) on total acid, viscosity, syneresis, water content and water holding capacity. The results of the study can be concluded that the best yoghurt set quality was by adding 3% kimpul starch and 48 hours incubation time is able to improve the quality of yogurt set optimally.